Enhanced Solubility and Antitumor Activity of Annona Squamosa Seed Oil via Nanoparticles Stabilized with TPGS: Preparation and In Vitro and In Vivo Evaluation - Hui Ao; Likang Lu; Manzhen Li; Meihua Han; Yifei Guo; Xiangtao Wang (MDPI AG, 2022)
Annona squamosa seed oil (ASSO), which is a waste product in the extraction of annonaceous acetogenins (ACGs), displays good antitumor activity against a variety of tumor cells. However, ASSO is insoluble and has low bioavailability. In order to improve the solubility and application value of ASSO, the seed oil nanoparticles (ASSO-NPs) were successfully prepared only using TPGS as a stabilizer. ASSO-NPs obtained were spherical with a uniform size (less than 200 nm). ASSO-NPs showed the good storage stability at 25 ± 2 °C and were suitable for both oral administration and intravenous injection. The antitumor study in vitro and in vivo demonstrated more enhanced antitumor efficacy of ASSO-NPs than free ASSO. The ASSO-NPs group (15 mg/kg) had the highest tumor inhibition rate (TIR) of 69.8%, greater than the ASSO solution (52.7%, 135 mg/kg, p < 0.05) in 4T1 tumor-bearing mice. The in vivo biodistribution data displayed that the fluorescence intensity of ASSO/DiR-NPs in tumor was similar to that in liver in the presence of the reticuloendothelial system. Besides, the relative tumor-targeting index (RTTI) of (ACGs + ASSO)-NPs was 1.47-fold that of ACGs delivered alone, and there is great potential in ASSO-NPs as tumor-targeted delivery vehicles. In this study, ASSO-NPs were firstly prepared by a very simple method with fewer excipients, which improved the solubility and antitumor activity of the ASSO, displaying a good prospect in the in vivo delivery of natural bioactive compounds.